Some aspects of using expressive arts-therapies in education and rehabilitation - Miholić Damir; Martinec Renata (Specijalna Edukacija i Rehabilitacija, 2013)
Contemporary approaches in different fields of expressive arts-therapies (art-therapy, music therapy, dance movement therapy, bibliotherapy, psychodrama and drama therapy) are presented in this article. In that way, theoretical background, some elements of observation and assessment, as well as specific methods of therapy interventions are described. Relevant knowledge about different aspects of expressive art-therapies is presented by reviewing some recent references and results of different investigations. Results of previous researches pointed out that expressive arts-therapy may have positive influence on different aspects of psychosocial functioning. Also, further investigations are needed in order to achieve best practice in different fields of education and rehabilitation.